Pengaruh Desain Iklan dan Intensitas Iklan Terhadap Awareness Konsumen (Studi Kasus pada Media Sosial Produk Kosmetik Skintific) - Angeline Wong (SCIENTIA JOURNAL, 2026)
This study examines how advertising design and advertising intensity influence consumer awareness of the Skintific skincare brand on social media. The research problem arises from the growing competition in the beauty industry and the need for brands to build recognition through effective digital communication strategies. Advertising design is conceptualized as a persuasive marketing communication component that conveys messages through visual elements, typography, colors, and layout, while advertising intensity refers to the frequency of message exposure that reinforces consumer recall. Consumer awareness is positioned within the cognitive stage of the Hierarchy of Effects model, where individuals recognize and recall a brand before progressing to affective and behavioral responses. This research employs a quantitative explanatory survey involving 270 respondents aged 15–49 years in Batam City, selected through random sampling. Data were collected using an online Likert-scale questionnaire and analyzed with multiple linear regression using SPSS. The results indicate that both advertising design and advertising intensity have significant and positive effects on consumer awareness, either partially or simultaneously, demonstrating that Skintific’s social media advertising strategy effectively increases consumer brand recognition.